2020
DOI: 10.1097/nrl.0000000000000307
|View full text |Cite
|
Sign up to set email alerts
|

Neurological Manifestations of SARS-CoV-2

Abstract: Background: Coronavirus disease 2019 (COVID-19) pandemic started as an outbreak in China and soon crossed borders to affect the populations in all countries of the world. During the initial course of the disease, COVID-19 was perceived as a pneumonia-like illness. However, recent findings of COVID-19 patients suggest that the virus has the potential to disseminate to different tissues and organs, and cause significant complications. Summary: Neurologica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 40 publications
0
10
0
1
Order By: Relevance
“…A letter dating from June 2020 ( 12 ) reported that a third of their discharged COVID-19 patients showed a dysexecutive syndrome consisting of “inattention, disorientation, or poorly organized movements in response to command” (Third paragraph). As more unusual symptoms emerged it became gradually clear that COVID-19 could affect a wide variety of organs and tissue ( 13 15 ).…”
Section: Introductionmentioning
confidence: 99%
“…A letter dating from June 2020 ( 12 ) reported that a third of their discharged COVID-19 patients showed a dysexecutive syndrome consisting of “inattention, disorientation, or poorly organized movements in response to command” (Third paragraph). As more unusual symptoms emerged it became gradually clear that COVID-19 could affect a wide variety of organs and tissue ( 13 15 ).…”
Section: Introductionmentioning
confidence: 99%
“…However, these findings do not imply that the nervous system is only directly affected by SARS-CoV-2. Indirect effects on the central and peripheral nervous system through injury to other organ systems are also reported [ 169 ]. Some underlying conditions and risk factors have been linked to the severity of the reported neuropathological conditions that may partially explain the selectivity in certain patients infected by SARS-CoV-2.…”
Section: Discussionmentioning
confidence: 99%
“…We observed that several articles within this category reviewed the neurological manifestations and complications of severe COVID-19, reporting skeletal muscle damage associated with myalgia and elevated levels of CK in severely ill patients ( Ahmad and Rathore, 2020 ; Benny and Khadilkar, 2020 ; Drożdżal et al, 2020 ; Fotuhi et al, 2020 ; Khan et al, 2020 ; Nepal et al, 2020 ; Pinzon et al, 2020 ; Puccioni-Sohler et al, 2020 ; Sheraton et al, 2020 ; Andalib et al, 2021 ; Harapan and Yoo, 2021 ; Moghimi et al, 2021 ; Orsucci et al, 2021 ; Quraishi et al, 2021 ). It was also reported cases of muscle pain associated with muscle denervation atrophy, suggesting Guillain-Barré syndrome, an autoimmune peripheral nervous system disease, as a sequel of the SARS-CoV-2 infection ( Aksan et al, 2020 ; Bahouth et al, 2021 ; Meyer-Frießem et al, 2021 ).…”
Section: The Lack Of Musculoskeletal Data Related To Mild To Moderate...mentioning
confidence: 99%